An investigation into the curing of urushi and tung oil films by thermoanalytical and mass spectrometric techniques. (December 2016) - Tamburini, Diego; Sardi, Dario; Spepi, Alessio; Duce, Celia; Tinè, Maria Rosaria; Colombini, Maria Perla; Bonaduce, Ilaria
Abstract: Urushi is the oldest and most precious lacquer used since antiquity in East Asia. For artistic purposes, in order to obtain suitable rheological properties, the lacquer is usually mixed with a vegetable oil. In this work we investigated the curing process of urushi/tung oil mixtures in order to highlight the chemical interactions at the molecular level between the two materials. A multi-analytical approach was adopted, based on thermogravimetry (TG), differential scanning calorimetry (DSC), gas chromatography-mass spectrometry (GC-MS), evolved gas analysis-mass spectrometry (EGA-MS), analytical pyrolysis coupled with gas chromatography and mass spectrometry (Py-GC-MS) and high performance liquid chromatography-mass spectrometry (HPLC-MS). Fresh and aged mixtures were analysed and the results were compared with those obtained from the analysis of the individual materials. The data highlighted that different polymerisation and oxidation mechanisms take place in oil/urushi mixtures compared to the pure materials. Py-GC-MS and GC-MS showed that the profile of aliphatic mono- and di-carboxylic acids was drastically different for the aged film of pure tung oil compared to the mixtures. The ratio between the relative content of azelaic and palmitic acids was much lower in the mixtures than in the pure oil, highlighting a lower level of oxidation. On the other hand, the relative content of short chain carboxylic acids, which are produced by pyrolysis of the cross-linked oil network, increased as the concentration of urushi in the mixtures increased, thus indicating an increasing level of reticulation. HPLC-MS showed a relatively higher amount of triglycerides with hydroxylated fatty acids – the intermediate oxidation product of polyunsaturated fatty acids - in the mixtures with respect to pure tung oil.